Teacher perceptions on mathematically gifted : A survey of mathematics teachers in Motheo and Xhariep districts’ primary schools of Free State Province - Van Wyk, Motshidisi Gertrude ([Bloemfontein] : Central University of Technology, Free State, 2018)
In South Africa, schools are defined as full-service schools (FSS) that are inclusive and welcoming of learners to develop their full potential irrespective of their background, culture, abilities or disabilities, their gender or race (Department of Basic Education, 2014). However, gifted learners are found in mainstream classrooms where teachers must deal with a wide diversity of learners. Empirical evidence shows that teachers are trained on inclusive education, but the interpretation of inclusive education is that of meeting the needs of learners who are falling behind. This interpretation excludes gifted learners confirming (Oswald & de Villiers, 2013) assertions that teachers are not trained on gifted education. Yet the outstanding creativity of a small percentage of the population (gifted learners) has been described as mankind’s ultimate human capital asset. This study adopted Gagné’s Differentiating Model of Giftedness and Talent (DMGT) which sensitizes researchers about the developmental process of the student’s potential that could be affected negatively or positively by environmental and intrapersonal catalysts. Consequently, if the developmental process is affected negatively, it becomes poor and result in hindering the gifted student to become talented. Such student’s inherent gifts will go to waste but if nurtured and developed, such potential (gifts) will reveal his or her talent (Gagné, 2007). Based on this concern, this study aimed at investigating perceptions of foundation phase teachers from the Motheo and Xhariep districts’ primary schools of the Free State toward mathematically gifted learners. This study was guided by Gagné’s fifth commandment about the education of gifted students that suggests the need for earliest intervention in developing talent into gifts – as early as kindergarten or first grade (Gagné, 2007). This study investigated foundation phase teachers’ preparedness in terms of catering for the needs of mathematically gifted learners in their regular classrooms. It also investigated principals’ perceptions toward gifted education through inclusive education that is currently practiced in mainstream classrooms. The study followed a mixed method approach. Purposive sampling was used to select the 118 mathematics teachers who took part in the study. Data was collected by means of a three-point Likert scale questionnaire and the face-to-face structured interview schedule for teachers and principals respectively, from all twenty selected primary schools. All the data, collected in this study, collected from questionnaires and interviews, were organised within the context of the research questions using thematic analyses drawn from to provide coherence on the findings of this study (Cohen, Manion & Morrison, 2011). Regarding teacher preparedness, the results show that 94 teachers were trained to teach Numeracy, 91 teachers were trained to teach Literacy and 83 teachers were trained to teach Life Skills. The results also show that 64% of teachers perceived themselves as being competent enough to teach the gifted learners in their regular classrooms. However, 88% of teachers expressed the need for higher education institutions to include content on gifted education in their courses. The results further, show that 35% of principals encourage teachers to differentiate teaching methods or strategies and resources in their lesson planning, to facilitate effective inclusive education. However, differentiation was with reference to struggling learners not for gifted learners. These results are similar to what Mhlolo (2015) found in terms of the implementation of an inclusive education policy in South Africa being a main concern which is affected by a number of factors such as lack of training.
Thesis (Masters’ Degree in Education) -- Central University of Technology, Free State, 2018
Keywords: Central University of Technology, Free State -- Dissertations; Mathematically gifted learners; Teachers' strategies; Inclusive classrooms